Evaluasi Pengembangan Sistem Informasi Penerimaan Mahasiswa Baru Berbasis Workflow Otomatis Menggunakan Pendekatan Research and Development - Muhammad Ichsan M; Muh Salim; Sulistiawati Rahayu Ahmad; Ali Asgar Zainal Abidin; Abdul Ma'arief Al Imran (JSAI (Journal Scientific and Applied Informatics), 2026)
The New Student Admissions (PMB) process is a strategic endeavor that influences the quality of university entrants. Nonetheless, in several colleges, particularly in remote regions, the execution of PMB remains manual, which may lead to issues regarding efficiency, accuracy, and openness in data management. This study seeks to create and assess an automated workflow-oriented PMB information system to enhance PMB management at the Muhammadiyah Selayar Institute of Technology, Science, and Business. The system development employs the Waterfall methodology, encompassing the phases of requirements analysis, design, implementation, and system testing. Evaluation is conducted by assessing the validity, practicality, and efficacy of the system with the participation of internal users as evaluators. The evaluation results demonstrated a validity rate of 100%, practicality of 95.83%, and effectiveness of 89.56%, demonstrating the system's feasibility for supporting the PMB process. This system can systematically combine the registration process, document verification, selection, and results announcement. This research contributes an automated workflow implementation model within the PMB information system, enhancing process management efficiency and facilitating the oversight of PMB activities. While the test remains confined to the institution's internal setting, the findings of this study are anticipated to serve as a benchmark for the establishment of a comparable PMB system in universities with analogous attributes.